Neoliberal narratives and the logic of abstinence only education: why are we still having this conversation?. Issue 3 (3rd April 2018) - Clark, Lauren; Stitzlein, Sarah M.
ABSTRACT: Given the lack of citizen or medical support for abstinence-only education, we ask how abstinence-education maintains such a stronghold in America and other Western democracies' public policy and consciousness. Our response has three parts. In the first, we outline the disproportionately negative health outcomes of sex education experienced by female, impoverished, ethnic and racial minorities, and LGBT youth. Next we address prominent narratives in sex education. We use the work of Pierre Bourdieu as a frame to understand neoliberal narratives and the accrual of cultural capital. Next we address two specific narratives in sex education, both of which align with broad tenets of neoliberal thought: the first of these is a focus on individual responsibility at the expense of understanding broader social structures. The second questions the role of education in a democratic nation that privileges the private over the overall health of the citizenry. In closing, we highlight comprehensive alternatives to sex education that can better prepare healthy individuals and democracy.